GEOIDAL UNDULATION AND GRAVITY ANOMALY AROUND THE JAPANESE ANTARCTIC STATIONS ESTIMATED FROM BOTH SATELLITE ALTIMETER DATA AND SURFACE GRAVITY DATA - フクダ, ヨウイチ; セガワ, ジロウ; カミヌマ, カツタダ; FUKUDA, Yoichi; SEGAWA, Jiro; KAMINUMA, Katsutada (National Institute of Polar Research, 1990)
P(論文) Gravity anomalies and geoidal undulations around the Japanese Antarctic stations (60°-80°S, 20°-50°E) have been newly estimated using both satellite altimeter data and surface gravity data. The method employed for the estimation is the Least Squares Collocation by which both data can be dealt with simultaneously with exact estimates of formal errors. The data employed are surface gravity data mainly from JARE and GEOSAT altimeter data. These data are the most updated ones in the region, and the results obtained should be the most reliable. We believe that the results should contribute to both geophysical and geodetic applications in the region because there have been few gravity anomaly maps and no geoidal undulation map so far. departmental bulletin paper